Decision Support System Scholarship Using Profile Matching - Ardiane Rossi Kurniawan Maranto; Suwitno Suwitno; Andri Wijaya (Tech-E, 2022)
Education is very necessary in social life. Education has a role that will improve the quality of resources to be able to have the competencies needed in an increasingly advanced and developing era. Giving this scholarship will also greatly help someone in pursuing and even getting an education. Scholarships must also be done objectively, not just subjectively. Because the problems that occur when objectively granting scholarships may not be in accordance with the target of the scholarship award. Scholarships must also be given according to the right criteria so that the scholarship grants get maximum results for the administrators and scholarship recipients. The research was conducted using the Profile Matching method with Interpolation at the Indonesian Christian Church Pos Cikoleang, it will require decision makers to determine the weight value for each criterion. The results issued by the system are the congregations that are accepted and rejected in the scholarship application. and the system can provide scholarships with an accuracy rate of 78%.